Clustering Debitur PNPM Mandiri Perdesaan Kecamatan Simeulue Timur Dengan Metode K-Means Menggunakan Matlab - Vira Anjani; Yuyun Dwi Lestari; Rismayanti (Universitas Harapan Medan, 2021)
People who need loan funds to open a business. Every regional and central leadership makes the poor as the main goal that must be resolved. Fund loan assistance is needed to open a business. Based on data from the women's special savings and loan group (SPP) in the Simeulue Timur District, Simeulue Regency, it shows several types of businesses, loan nominal and loan arrears. This study groups (clusters) members of women's special savings and loan groups (SPP) lending using the K-Means method. This method consists of 3 criteria, namely the type of business, nominal loan and loan arrears. In this study, group members who are entitled to get a loan are group members who have the highest cluster value. A scoring system that is very feasible to get a loan using the data mining method Clustering K-Means. This system can be used as a clustering method to assist decisions in determining women's special savings and loan groups (SPP).